Relationship between the asymptotic behavior of exponents of a multidimensional exponential series and the asymptotic behavior of its coefficients in a neighborhood of singular points - Makarov, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study the relation of the asymptotic behavior of the coefficients of multidimensional exponential series to the asymptotic behavior of its sum by using theR-order of the growthp QR (a 1,...,a n ) in an octantQ(a 1,...,a n ).